2011
DOI: 10.1111/j.1447-0756.2011.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent high glucose on BeWo choriocarcinoma cells in culture

Abstract: These data indicate that intermittent high glucose is more deleterious to BeWo cells than continuous high-glucose conditions. Although further in vitro and in vivo study is necessary, excess fluctuation of glucose levels in the placental circulation might be involved in the impairment of placental development leading to the placental dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…High-glucose treatment tended to increase BeWo cell counts modestly in the current study setting, although Weiss et al 26 and Masumoto et al 27 both reported that trophoblast growth was inhibited by in vitro hyperglycemia. Interestingly, expression of the cellular proliferative marker KI67 was significantly dampened in high glucose, whereas another proliferative marker PCNA was unchanged, despite the modest increase in cell counts.…”
Section: Discussioncontrasting
confidence: 58%
“…High-glucose treatment tended to increase BeWo cell counts modestly in the current study setting, although Weiss et al 26 and Masumoto et al 27 both reported that trophoblast growth was inhibited by in vitro hyperglycemia. Interestingly, expression of the cellular proliferative marker KI67 was significantly dampened in high glucose, whereas another proliferative marker PCNA was unchanged, despite the modest increase in cell counts.…”
Section: Discussioncontrasting
confidence: 58%
“…Trophoblast cell viability can be suppressed by high glucose, but the understanding about the underlying mechanisms remains limited. A previous study investigated the effects of high glucose on trophoblast BeWo cells and stated that the inhibited cell proliferation induced by high glucose might be related with dysregulation of heparin-binding-EGF (HB-EGF), which is a known survival factor for trophoblasts [ 33 , 34 ]. In another study regarding the differentially expressed miRNA in GDM, high glucose induced the upregulated miR-137 in trophoblasts, and the miR-137/PRKAA1/IL-6 axis was proposed to mediate the inhibitory effects of high glucose on trophoblast cell proliferation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raw CT values were processed using the DCT method relative to the geometric mean of two reference genes, ACTB and GAPDH. These reference genes have been widely utilized in other studies of choriocarcinoma cell line mRNA expression levels (Lee et al, 2004;Chiu et al, 2007;Li et al, 2008;Masumoto et al, 2011;Mparmpakas et al, 2012;Chen et al, 2013). DCT values generated relative to ACTB and GAPDH were highly correlated in all assays included in this study (Supplementary data, Fig.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 98%